2020
DOI: 10.1002/slct.202002446
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal‐Free, Base‐Induced Arylation of Amino Acids: Synthesis of N‐(para‐Substituted phenyl)amino‐2‐carboxylic acids

Abstract: A metal‐free aryl amination reaction of aryl halides and amino acids; with the amino acid serving as the nucleophilic aminating agent, is reported. The reaction was achieved by the condensation of various aryl halides 1 with cyclic and acyclic amino acids 2, in the presence of a cheap and readily available base, potassium carbonate, in refluxing ethanol/water solution (1 : 1) for 3 h, under simple operating conditions. The products, N‐(p‐substituted phenyl)‐amino‐2‐carboxylic acids 3–12, were obtained in isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Infrared spectra were recorded on a Perkin Elmer Universal (ATR Spectrum 100) FT-IR spectrometer. [20,21] To a clean round-bottomed flask charged with a condenser, amino acid 2a-g (12 mmol) in C 2 H 5 OH/H 2 O (1:1) (20 mL) and K 2 CO 3 (3.5 equiv.) was added.…”
Section: Experimental 21 Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrared spectra were recorded on a Perkin Elmer Universal (ATR Spectrum 100) FT-IR spectrometer. [20,21] To a clean round-bottomed flask charged with a condenser, amino acid 2a-g (12 mmol) in C 2 H 5 OH/H 2 O (1:1) (20 mL) and K 2 CO 3 (3.5 equiv.) was added.…”
Section: Experimental 21 Materials and Methodsmentioning
confidence: 99%
“…In this study, therefore, we report the synthesis and antibacterial evaluation of N-aryl amino acids against eight bacterial strains: Bacillus subtilis (ATCC 6633), Streptococcus pneumoniae (ATCC 33400), Staphylococcus aureus (ATCC 25923), Staphylococcus epidermidis (ATCC 14990) Enterobacter cloacae (ATCC 43560), Escherichia coli (ATCC 25922), Proteus mirabilis (ATCC 43071), and Klebsiella oxytoca (ATCC 13182). The N-aryl amino acids were obtained from different 4-substituted fluorobenzene and different amino acids (Scheme 1), using a modified Ullman-type coupling reaction [20]. A synthesis report has been published.…”
Section: Introductionmentioning
confidence: 99%
“…The requisite N-(4 0 -nitrophenyl)-L-prolinamides 4a-w were accessed via a two-step reaction as shown in scheme 1. The first step involved a base-catalysed condensation reaction, using potassium carbonate in refluxing ethanol-water (1 : 1) solution, as earlier reported [21,22], to furnish N-(4 0 -nitrophenyl)-Lprolines 3a-c in 70-90% yield. It was found that refluxing the reaction in ethanol-water (1 : 1) solution royalsocietypublishing.org/journal/rsos R. Soc.…”
Section: Chemistrymentioning
confidence: 99%